(untitled) (Raparin Journal of Humanities (RJH), 2025)
This study is entitled conceptual metaphor of time in Kurdish. It attempts to indicate the perception and worldview of Kurdish concerning time as a cognitive concept in Kurdish language, in which time can be seen as a moving entity. In addition to that, the study demonstrates the emergence and experience of time concept in related to human perception, psychological and social aspects. Hence, it focuses on the way of reflecting conceptual metaphor of time in Kurdish. The data of the study have been taken from the daily use conversations of the Central Kurdish speakers. The study draws upon cognitive models of time for the analysis of the data within the framework of cognitive semantics which is proposed by Lakoff and Johnson. Moreover, the study identifies the way of reflecting experience as a basic principle of cognitive semantic on the Kurdish individual thoughts as well as the influence of human perception and self-perceptions in Kurdish expressions in which time moving and ego depletion vice versa are shown in a balanced way. Additionally, the way of time perception which is measured by time duration and changing (lengthening and shortening) in terms of inner sensory experience and individual perception is another point presented in this study, along with unfolding the location of temporary events according to time series model and comparing with each other.